Virtual and augmented reality application in production engineering teaching-learning processes - Anjos,Fernando Elemar Vicente dos (2020)
Abstract Paper aims Structure virtual and augmented reality applications in engineering teaching-learning processes, with emphasis on production engineering, highlighting application gaps. Originality First studies that, to which subjects applied virtual and augmented reality in engineering teaching-learning processes, the gaps of application in production engineering, and a discussion about the impacts. Research method The research method applied was the systematic literature review. Main findings Structuring of virtual or augmented reality applications in engineering, discussion about the application in production engineering, opportunities for future research, how low application affects graduated professional education, consequently, organizational competitiveness. Implications for theory and practice The applications of virtual and augmented reality bring developing student skills more actively and cognitively, making training more complete, increasing their skills, and supporting the competitiveness of organizations through professionals who can contribute more broadly and effectively.